Inventor® self-paced eCourse : Autodesk Inventor : ebook - Baumback, Wally; Vancouver Community College; BC Open Textbook Project; BCcampus (Vancouver Community College, 2020)
"This eBook contains self-paced learning modules that were written as a tool to guide and teach students to master Inventor. No two students learn at the same pace, therefore, the modules were written as competency-based bite-size pieces to allow students to work at their own pace. This book can be used in correspondence courses, online courses, instructor-lead classes, or by individuals teaching themselves to use Inventor in their own home or office. An editable, Pressbooks version of this resource is under development."--BCcampus website.
This work is licensed under the Creative Commons Attribution International CC-BY.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes index.
"Intended for Autodesk Inventor 2020 and 2021 but useable with earlier releases."
Description based on online resource; title from pdf title page (viewed on December 22, 2020).
Keywords: Autodesk Inventor (Electronic resource); Engineering graphics -- Data processing; Engineering models -- Data processing; Computer-aided design -- Computer programs; Electronic books